Implementation of the Scaffolding Method in Improving Fiqh Learning Outcomes on Zakat Fitrah Material for Pudji Hardjo Prambon Elementary School Students - Himawati, Widatul; Larasati, Wati; Mastika, Winda; Fitriani, Widia; Fauzy, Wildan Taufiq (Journal of Media and Learning Technology, 2025)
This study aims to analyze the application of the scaffolding method in improving Fiqh learning outcomes on Zakat Fitrah material at MI Pudji Hardjo Prambon, Tugu District, Trenggalek Regency. The scaffolding method is a learning strategy that provides temporary assistance to students according to their level of understanding until they are able to learn independently. This study uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation to determine the effectiveness of the application of the scaffolding method in the learning process. The results of the study indicate that the application of the scaffolding method effectively helps students understand the concept of Zakat Fitrah better. Through stages such as providing guidance, guiding questions, and gradual exercises, students are more active in the learning process. In addition, this method also contributes to improving learning outcomes, which are reflected in the increase in student grades and their ability to explain the concept of Zakat Fitrah independently. Thus, the scaffolding method can be used as an effective strategy in teaching Fiqh, especially on materials that require in-depth understanding such as Zakat Fitrah.